Study of Main Factors Caused Incompatibility of the Purse Seine Fisherman Zone in Panyula Village, Bone Regency, South Sulawesi Based on Regulation of the Minister of Marine and Fisheries Number 71 of 2016 - Hawati; Angkasa Putra; Herianto Suriadin; Sarifah Aini; Nasrun Nurma; Rakhma Fitria Larasati (International Journal of Science and Society, 2022)
Regulation of the Minister of Marine Affairs and Fisheries of the Republic of Indonesia Number 71/PERMEN.KP/2016 concerning Fishing Paths and Placement of Fishing Equipment in the Fisheries Management Area of ​​the Republic of Indonesia in article 22 paragraph (1) that the placement of fishing gear and fishing aids in WPP RI is adjusted to the nature of fishing gear. Referring to these regulations, this research was conducted to examine the main factors causing the ignorance of the purse seine fishing zone for fishermen in Panyula Village, Bone Regency, South Sulawesi. This research was conducted from November 2016 to March 2017 in Panyula Village, which is the fishing base area of ​​purse seine fishermen and the waters of Bone Bay. This study uses a combination of survey and case study methods. This study uses two types, namely primary data and secondary data.The analysis of the factors causing the non-conformance was analyzed descriptively, namely comparing the average productivity of ring seines that catch in the designated zone and ring seines that catch in zones that are not according to their designation according to Minister of Marine Affairs and Fisheries Regulation Number 71 of 2016. After the study, the main cause of non-compliance with the Regulation of the Minister of Maritime Affairs and Fisheries Number 71 of 2016 is the high productivity of ring trawl units that carry out fishing on non-designated fishing lanes compared to ring trawl units that catch on correct fishing routes.